Pengembangan Sistem Informasi Bimbingan Konseling Siswa Pada SMP Negeri 1 Panarukan - Ahmad Taufiq Hidayatullah; Fajar Pradana; Mochammad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
SMP Negeri 1 Panarukan has one goal, namely the establishment of a students' noble character. To achieve this objective, the codes of conduct and counseling services were established. Based on the interview, there are some problems in the counseling services. Firstly, many violation points are not accumulated because the point record is still manual, so the sanctions given are not appropriate. This affects the results of student character values that require the total violation points as the indicator. Secondly, the ineffectiveness of parent notification letter which is rarely given by students to their parents. Lastly, the input process of the counseling services that seems to use too much paper. Based on these problems, it can be given a solution to develop an information system that has the function to overcome these problems. The method used in the development of the system is the waterfall method which includes needs analysis, design, implementation, testing, and maintenance. While in the testing process, basis path testing, validation testing, and testing compatibility are used. The results of basic path testing are the two functions having a structure that is easy to understand and easy to implement and 1 function having a more complex structure. The result of the validation testing is a software function that can be run in accordance with its functionality. The results of the compatibility testing is the software that can be used in 10 different types of browsers.